Entre rios, um estudo do Sistema Educacional do Ensino Presencial Mediado por Tecnologias em uma Comunidade no Município de Careiro da Várzea-AM, Possibilidades e Desafios - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
This research analyzes the educational model of the State System of Face-to-Face Teaching Mediated by Technology (SEEPMT) in the State of Amazonas, focusing on the challenges and possibilities of a public policy in the territory of waters, based on a case study at the Julieta Falcão de Oliveira Municipal School, Nossa Senhora Aparecida Community, Costa do Marimba - Municipality of Careiro da Várzea-AM. The investigation seeks to understand the impacts of this teaching model on the daily lives and the teaching-learning process, considering the context of rural education and the reality of a riverine community. The objective is to analyze the contributions, challenges, and perspectives of the SEEPMT for education, taking into account the specificities of cyberspace, time, and the networks of the subjects and actors involved. Among the problems listed; what are the implications and impacts of this educational model for the community? Considering the right to quality education and the challenges of infrastructure, accessibility, connectivity, and interaction with the local reality? The research is of a quantitative-qualitative nature, with a phenomenological case study approach. The methods used were: bibliographic review, analysis of documentary and educational legislation, field work with participant observation, semi-structured interviews with professionals from the Media Center (CEMEAM), teachers, and students, and collection of written reports and mind maps from students. The data analysis was based on the Analysis of reports and narratives, using categories that reflect the central questions of the research: The SEEPMT as a public policy and its application in the Amazonian context; The perception of the subjects; The challenges and possibilities for improving the program; private partnerships. The research also highlighted the potential of the SEEPMT to democratize access to education in "remote" areas, but also revealed the need for adaptations and improvements in serving the realities of the communities of the State of Amazonas. Because among the main difficulties identified, we have; the precarious infrastructure of schools at the front line, the difficult access to the internet and electricity, the lack of adequate equipment, dialogue, and communication, lack of supporting teaching materials, the urgent need for a reformulation of this teaching model in force, considering the quality of education and teaching in contexts of vulnerabilities. The data analysis brought to the fore the discussion of the social function of the school, the importance of public policies and the need for dialogue and participation of the community and the target audience of education in the debate and decision-making. The study also shows that the program, although it represents an important initiative for the universalization of access to education, still faces challenges to ensure the quality and equity of education, as the validated and reproduced institutional discourse imposes on the territory the blame for the omission and inertia of the State to act. Therefore, it is essential that this type of policy be constantly monitored and reassessed, with a focus on structural investments that effectively meet the needs of the population and promote quality education for all.
Entre Rios: A Study of the Educational System of Technology-Mediated Face-to-Face Education in a Community in the Municipality of Careiro da Várzea-AM, Possibilities and Challenges
Keywords: CIENCIAS HUMANAS: EDUCACAO; Educação; Ensino Presencial com Mediação Tecnológica; Políticas públicas; Ciberespaço